Concept of Resolving State Administrative Disputes Related to Environmental Issues from the Perspective of Substantive Justice - Imam Alfurqan; Suntarajaya Kwangtama Tekayadi; Khalid Prawiranegara (Sean Institute, 2026)
The resolution of administrative disputes related to environmental issues has increasingly demonstrated responsiveness towards ensuring ecological justice. Efforts to fulfill ecological justice within the State Administrative Court (PTUN) have started to be reflected in the judges' considerations, which weigh the interests of sustainability and the balance between human and environmental interests, both in the present and in the future. This paper will explore two main issues: (1) whether the practice of resolving state administrative disputes related to environmental issues in Indonesia reflects substantive justice, and (2) how the concept of state administrative dispute resolution related to environmental issues can guarantee the achievement of substantive justice in the future. The findings of this study indicate that (1) several PTUN rulings have taken environmental justice into account as the core of their reasoning, by considering three key principles of environmental justice, such as intergenerational equity, sustainable environment, and the polluter pays principle; (2) there is a need for the internalization of environmental protection principles in state administrative disputes, similar to the position of the principles of AUPB (Administrative Principles of Good Governance) as a benchmark for assessing government actions. The internalization of environmental principles can be implemented through several steps: first, reformulating positive law by revising the PTUN Law to explicitly grant judges the authority to examine the ecological substance of cases; second, enhancing judges' capacity through environmental education; and third, shifting the legal enforcement paradigm to recognize the environment as a legal subject with rights to be protected